Pemblokiran Aplikasi Asing sebagai Perlindungan Usaha di Indonesia dan Penerapan Prinsip National Treatment - Valentino Satrio Kusumo (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study discusses the blocking of a foreign e-commerce platform called the 'X' application from China by the Indonesian Government in October 2024. The blocking was carried out as a form of protection for Micro, Small, and Medium Enterprises (MSMEs) affected by the predatory pricing practices of the application. The problems discussed are whether this policy really protects MSMEs and how this policy is reviewed from the principle of National Treatment in international trade law. The method used is normative juridical with a regulatory analysis approach. The results of the study show that the blocking policy has a legal basis through PP No. 71 of 2019 concerning PSTE and PP No. 80 of 2019 concerning PMSE. The government does not discriminate against the 'X' application because the rules apply equally to all business actors. A similar case occurred with TikTok Shop which was blocked for making indirect sales without representatives in Indonesia. TikTok was only allowed to operate again after complying with regulations, including acquiring most of Tokopedia's shares and moving transactions to official e-commerce.